Happiness, virtue and wisdom: elements of ancient Greek philosophy in Islamic advice literature - Belhaj, Abdessamad (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2024)
This essay examines the profound influence of ancient Greek philosophy on Islamic advice literature, particularly in political ethics and governance. It aims to trace the integration of Greek philosophical ideas into Islamic advice literature, focusing on four key areas: Plato's theory of happiness, Aristotle's virtue ethics, the concept of "the three governances," and the ideal ruler-advisor relationship. Employing a meticulous analysis of a dozen Islamic sources from the tenth to the fifteenth centuries, it uncovers the extent of Greek thought's impact. Findings reveal that Islamic political elites, including philosophers, secretaries, religious scholars, and historians, adopted and adapted Greek philosophical theories to align with Islamic political goals and strategies. Plato's notions of happiness through just rule and the pursuit of knowledge and justice are echoed in the works of Islamic luminaries. Aristotle's virtue ethics, emphasizing prudence, temperance, courage, and justice, are seamlessly woven into Islamic governance literature. The concept of "the three governances" reflects Aristotelian governance principles, while Greek gnomology is used to validate political concepts especially the ideal ruler’s wisdom, showcasing the rhetorical power of invoking Greek authorities. The study concludes that Greek elements were frequently combined with Arabic, Persian, and other influences in Islamic advice literature, suggesting caution in interpreting Islamic political ethics through an exclusive lens. The research underscores the convergence of cross-cultural ideas and the Islamization of Greek philosophy to support political demands within a religious framework.